Evaluation of IL-32 Levels in Gingival Tissue and Serum of Experimental Periodontitis Model (Annals of Medical Research, 2021)
Aim: Interleukin (IL)-32, a recently discovered proinflammatory cytokine, is demonstrated in several infectious diseases. The goal of this study is to investigate the levels of IL-6, IL-10 and IL-32 in gingival tissue and serum of rats with experimental periodontitis.
Keywords: Interleukin-32; Experimental Periodontitis; Gingiva; Serum.